Changing the sales conversation connect, collaborate, close - Richardson, Linda 1944- (McGraw-Hill Education, 2014)
CREATE BETTER, MORE EFFECTIVE CONVERSATIONS IN TODAY'S HYPER-DIGITAL WORLD. In this era of iPads, iPhones, and apps, sales communications may be growing, but sales conversations are dying--and so are too many sales. Globalization, the explosion in competition, the slow economy, and fast-emerging technologies all have changed buying habits. Salespeople can no longer rely on the traditional sales methodologies. They must change the conversation. A visionary of the consultative sales movement, Linda Richardson has again moved selling forward by reengineering the sales conversation. Purchasing has become a core competency for clients. They evaluate their options against checklists they carefully develop. Richardson helps you understand what is on their checklists and align your solutions with their business and personal priorities to help you win. Clients today are focused on business outcomes. They are interested in reducing risk. They turn to peers and social networks to self-educate before turning to salespeople. To engage them you must demonstrate that you know their world and that you are prepared with insights and ideas to add to what they already know. Richardson gives you five clear strategies and tools to help you do just that. You will create and shape opportunities, prepare and probe in an entirely new way, gain client consensus, and use sales process and tools to guide and accelerate closing.
Includes index. - Online resource; title from title page (Safari, viewed February 7, 2014)
Keywords: Selling; Customer relations; Vente; selling; BUSINESS & ECONOMICS; Sales & Selling